Lec 02

Download as pdf or txt
Download as pdf or txt
You are on page 1of 8

1

1.1

1.1.1

Fréchet 1

1.1.
X
d:X ×X →R

x, y, z ∈ X
(a) ( ) d(x, y) ≥ 0, d(x, y) = 0 ⇐⇒ x = y,
(b) ( ) d(x, y) = d(y, x),
(c) ( ) d(x, y) + d(y, z) ≥ d(x, z)
(X, d) d X

1.2. d(x, y) ≥ 0

1.3.
(X, d) A⊂X

diam(A) := sup d(x, y)


x,y∈A

A diam(A) < +∞ A A
diam(X) < +∞ (X, d)

(X, d)

1.4.
(X, d) x0 r
B(x0 , r) = {x ∈ X | d(x, x0 ) < r},
B(x0 , r) = {x ∈ X | d(x, x0 ) ≤ r},
S(x0 , r) = {x ∈ X | d(x, x0 ) = r}.

1 (René Maurice Fréchet 1878–1973)


Jacques Hadamard 1906
1.1

1.5.
(X, d) U ⊂ X. x∈U ε>0

B(x, ε) ⊂ U,

U ⊂X F ⊂X Fc = X \ F
F

1.6.
(1) ( ) X ,

 0 x = y,
d(x, y) =
 1 x=6 y.
(X, ddiscrete )
(2) (Rn ) X=R ,
d(x, y) = |x − y|.
¯ y) = min{|x − y|, 1} ( ¯ y) = |x−y|
d(x, d(x, 1+|x−y| ).
X = Rn ,
p
( ) d2 (x, y) = (x1 − y1 )2 + · · · + (xn − yn )2 .
(l 1 ) d1 (x, y) = |x1 − y1 | + · · · + |xn − yn |.
(l∞ ) d∞ (x, y) = sup{|x1 − y1 |, · · · , |xn − yn |}.
lp (1 ≤ p ≤ ∞)

dp (x, y) := (|x1 − y1 |p + · · · + |xn − yn |p )1/p .

p (R2 , lp )

2
1.1

(3) (RN )

X = RN := {(x1 , x2 , · · · , xn , · · · ) | xn ∈ R}2

lp ,
R d¯
( )
¯ n , yn ).
d((xn )n∈N , (yn )n∈N ) := sup d(x
n∈N

( ):

X
d((xn )n∈N , (yn )n∈N ) := 2−n d(x
¯ n , yn ).
n=1
lp
lp
(lp , 1 ≤ p ≤ ∞)
 !1/p 
 X 
X = lp (R) := (xn )n∈N kxkp := |xn |p < +∞ ⊂ RN ,
 
n

lp

d((xn )n∈N , (yn )n∈N ) = kx − ykp .

(Hilbert )
Y
X= [0, 1/n] ⊂ RN .
n

l2 (R) l2
(4) ( ) [a, b] C([a, b])
(L1 ) Z b
d(f, g) = |f (x) − g(x)|dx.
a

(L∞ )
d(f, g) = sup |f (x) − g(x)|.
x∈[a,b]

(L2 )
ÇZ b
å1/2
d(f, g) = |f (x) − g(x)| dx 2
.
a

Lp (1 ≤ p ≤ ∞)
ÇZ b
å1/p
d(f, g) = |f (x) − g(x)| dx p
.
a
[a, b] k

2 Y X = {f : X → Y }. YN Y
R , ω
RN .

3
1.1

W k,p
k Z
!1/p
X b
d(f, g) = |f (i) (x) − g (i) (x)|p dx .
i=0 a

(5) ( ) G S⊂G 3 S

d(g1 , g2 ) = min {n : ∃s1 , · · · , sn ∈ S ∪ S −1 g1 · s1 · · · sn = g2 }.

(6) ( ) G = (V, E) V

d(v1 , v2 ) = min {n : G n v1 v2 }.

(5) Caylay Γ(G, S)


(7) (p ) p . 0 6= x ∈ Q
r
x = pn
s
n, r, s ∈ Z s > 0. Q p

|x|p = p−n ( |0|p = 0),

Q p

d(x1 , x2 ) := |x1 − x2 |p .

(8) (Hausdorff ) Rn Hausdorff

d(A, B) = inf {ε ≥ 0 : A ⊂ Bε B ⊂ Aε },

Aε = {y ∈ Rn : ∃x ∈ A |x − y| ≤ ε} A ε-

1.7.
(X, d) Y ⊂X

dY := d|Y ×Y

Y

y1 , y 2 , y 3 ∈ Y ⊂ X
dY (y1 , y2 ) = 0 ⇐⇒ y1 = y2 .
dY (y1 , y2 ) = d(y1 , y2 ) = d(y2 , y1 ) = dY (y2 , y1 ).
dY (y1 , y3 ) = d(y1 , y3 ) ≤ d(y1 , y2 ) + d(y2 , y3 ) = dY (y1 , y2 ) + dY (y2 , y3 ).

3 G S ∪ S −1 S⊂G

4
1.1

f : Y → X, Y f (Y ) ⊂ X,
X dX Y

d(y1 , y2 ) := dX (f (y1 ), f (y2 )).

1.8.
(X1 , d1 ), (X2 , d2 ) ,

d((x1 , x2 ), (y1 , y2 )) := d1 (x1 , y1 ) + d2 (x2 , y2 )

X1 × X2 .

X1 × X2 (x1 , x2 ), (y1 , y2 ) (z1 , z2 )

d((x1 , x2 ), (y1 , y2 )) = 0 ⇐⇒ d1 (x1 , y1 ) = 0 d2 (x2 , y2 ) = 0


⇐⇒ x1 = y1 x 2 = y2 .

d((x1 , x2 ), (y1 , y2 )) = d1 (x1 , y1 ) + d2 (x2 , y2 ) = d1 (y1 , x1 ) + d2 (y2 , x2 )


= d((y1 , y2 ), (x1 , x2 )).

d((x1 , x2 ), (z1 , z2 )) = d1 (x1 , z1 ) + d2 (x2 , z2 )


≤ d1 (x1 , y1 ) + d1 (y1 , z1 ) + d2 (x2 , y2 ) + d2 (y2 , z2 )
= d((x1 , x2 ), (y1 , y2 )) + d((y1 , y2 ), (z1 , z2 )).


1.9.

»
d((x1 , x2 ), (y1 , y2 )) := d1 (x1 , y1 )2 + d2 (x2 , y2 )2

X1 × X2 . (X1 , d1 ), · · · , (Xn , dn )
1 ≤ p ≤ ∞, X1 × · · · × Xn lp
 1/p
dp ((x1 , · · · , xn ), (y1 , · · · , yn )) := d1 (x1 , y1 )p + · · · + dn (xn , yn )p .
Q∞
(Xn , dn ) n=1 Xn
1.6(3) dn

d¯n (x, y) = min{dn (x, y), 1}.


Q∞
n=1 Xn l∞

du ((xn )n∈N , (yn )n∈N ) = sup d¯n (xn , yn )


n∈N
Q∞
n=1 Xn

5
1.1

¶ Lipschitz

1.10.
(X, dX ) (Y, dY ) f : (X, dX ) → (Y, dY )
x1 , x 2 ∈ X

dX (f (x1 ), f (x2 )) = dY (x1 , x2 ),

f (X, dX ) (Y, dY ) .

1.11.
f : (X, dX ) → (Y, dY ) x1 , x 2 ∈ X

dX (f (x1 ), f (x2 )) = dY (x1 , x2 ),

f

f : (X, dX ) → (Y, dY ) (X, dX ) (Y, dY )


(f (X), dY )

1.12. Lipschit
f : (X, dX ) → (Y, dY ) Lipschitz L Lipschit
x1 , x 2 ∈ X

dX (f (x1 ), f (x2 )) ≤ LdY (x1 , x2 ).


1.13.

Id : R → R, x 7→ x.

R , d(x, y) = |x−y| ¯ y) = min{1, d(x, y)}


d(x,

Id : (R, d) → (R, d) ¯ → (R, d)


Id : (R, d) ¯

,
¯
Id : (R, d) → (R, d)

Lipschitz
¯ → (R, d)
Id : (R, d)

Lipschitz

6
1.1

1.1.2

1.14.
(X, d) (xn ) X X x0
ε>0 N ∈N n>N

d(xn , x0 ) < ε,
d
(xn ) d x0 xn −→ x0 .

1.15.
(X, dX ) (Y, dY ) f :X→Y
(1) X x0 (xn ) (f (xn )) Y
f (x0 ) f :X→Y x0 ∈ X
(2) f x0 ∈ X f .

1.16. f : (X, dX ) → R R

1.17.

f : (X, dX ) → (Y, dY ) x0 ∈ X
⇐⇒∀ε > 0, ∃δ > 0 ∀x ∈ X, dX (x, x0 ) < δ, dY (f (x), f (x0 )) < ε
⇐⇒∀ε > 0, ∃δ > 0 f (B(x0 , δ)) ⊂ B(f (x0 ), ε)

⇐⇒∀ε > 0, ∃δ > 0 B(x0 , δ) ⊂ f −1 B(f (x0 ), ε) .

Lipschitz

1.18.
(1) (X, d)

7
1.1

x̄ ∈ X,

dx̄ : X → R, x 7→ dx̄ (y) := d(x, x̄)

∀ε > 0, ∀x0 ∈ X, ∀x ∈ X d(x, x0 ) < ε,

|dx̄ (x) − dx̄ (x0 )| = |d(x, x̄) − d(x0 , x̄)| ≤ d(x, x0 ) < ε.

( dx̄ Lipschitz 1 Lipschitz .) □


A⊂X

dA : X → R, x 7→ dA (x) := inf{d(x, y) : y ∈ A}.

dA

|dA (x) − dA (y)| ≤ d(x, y).


X ×X 1.8 dX×X d : X ×X → R
(X × X, dX×X )
(2) X = C([a, b]) l∞

d(f, g) := sup |f (x) − g(x)|.


x∈[a,b]

Z Z b
: X → R, f 7→ f (x)dx
a

Z b Z b Z b
f (x)dx − g(x)dx ≤ |f (x) − g(x)|dx ≤ (b − a) · dX (f, g).
a a a

(3) X dX X (Y, dY )
f :X→Y
ε>0 δ=1 x, x0 ∈ X dX (x, x0 ) < 1
x = x0 dY (f (x), f (x0 )) = 0 < ε. □
f :Y →X
4
f
f : Y → X y0 δ > 0
dY (y, y0 ) < δ y∈Y dX (f (y), f (y0 )) < 1 dX
f (y) = f (y0 ) f y0 □

4 f :Y →X y0 ∈ Y δ>0 d(y0 , y) < δ y


f (y) = f (y0 ).

You might also like